Sistem Informasi Manajemen (SIM) Berbasis Website Pada Kanwil Kementerian Agama Provinsi Sulawesi Selatan - Fadliani, Fadliani (Pascasarjana Universitas Negeri Makassar, 2015)
This study aimed to describe the implementation of Management Information Systems (MIS)-based Office of the Ministry of Religious Affairs Website In South Sulawesi province that includes: managing input data, process data management, output management / information, as well as the factors supporting and inhibiting the Management Information Systems (MIS) Based Website at the Regional Office of the Ministry of Religious Affairs in South Sulawesi. The results showed that the Management Information Systems (MIS) based Office of the Ministry of Religious Affairs Website In South Sulawesi province in terms of data management to information as a public disclosure has been made, but not optimally, the management of data processing has been applied, but its realization is not maximized, output management / information has been accomplished, but not maximum, as well as supporting and inhibiting factors not fully in line with expectations.